What Does Success Look Like? Lessons from the Innovations in Community-Based Crime Reduction (CBCR) Program. (2nd July 2020) - Hipple, Natalie Kroovand; Saunders, Jessica; Allison, Kayla; Peterson, Jessica
Abstract: Using mixed methods, we examine how a cohort of twelve sites operationalized and adapted the Bureau of Justice Assistance's Innovations in Community-Based Crime Reduction (CBCR) grant program. CBCR is built around data, place-based strategies, neighborhood revitalization, and community partnerships. Community-based interventions are typically quite complex, embedding multiple mechanisms by which the intervention may succeed or fail. We examine fidelity to the program and its relationship to implementation success, as well as the achievements and challenges reported by the sites.